Strategi Pentahelix Pada Perencanaan Pariwisata di Desa Hegarmukti, Cikarang, Kabupaten Bekasi, Jawa Barat - Muhammad Alfan Hakim (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
At the present time, tourism in Indonesia is growing very rapidly. Therole of the stakeholder is very necessary for terms of planning a tourist destination because it can help to develop tourism potential in a village. This study focuses on discussing the pentahelix strategy in tourism planning in tourist villages. This study’s purpose is to determine strategy in tourism planning for Hegarmukti Village, Cikarang, Bekasi Regency, West Java, using pentahelix model from 5 stakeholders. This research used qualitative research methods. This study found the role for each stakeholders are: the academics focus on tourism planning based on current theories, the government focuses on policymakers in developing tourism potential, business people is as a nail in creating added value and maintaining surrounding economic growth, and the role of the community is to help manage tourism potential and the role of the media is to promote and help to inform the wider community about the tourism potential that exists in the village.As the result of all the analysis from stakeholders, there are 3 focussed strategies for Desa Wisata Hegarmukti, in term of developing tourist attraction through culture and nature, and also infrascturure and facility development.